How to Use Nematac® S against Pest Mole Crickets in Pastures - Norman C. Leppla; J. Howard Frank; J. A. Graesch (EDIS)
Revised! IPM-147, a 3-page illustrated fact sheet by N.C. Leppla, J.H. Frank, and J.A. Graesch, discusses the use of the proprietary formulation of insect-parasitic nematode Steinernema scapterisci for use against mole crickets, which can severely damage Florida pastures. Published by the UF Department of Entomology and Nematology, June 2010.